1992
DOI: 10.1002/bjs.1800790523
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of continence following rectopexy for rectal prolapse and recovery of the internal anal sphincter electromyogram

Abstract: Twenty-two patients with full-thickness rectal prolapse underwent ambulatory fine wire electromyography of the internal and sphincter (IAS), external and sphincter and puborectalis, together with anorectal manometry, using a computerized system. Examinations were performed both before and 3 to 4 months after rectopexy. The median (interquartile range (i.q.r.)) preoperative IAS electromyogram (EMG) frequency was 0.18 (0.05-0.31) Hz and the median (i.q.r.) preoperative resting anal pressure was 28 (15-64) cmH2O.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 8 publications
1
45
1
2
Order By: Relevance
“…The fact that the internal sphincter plays an important role in continence in rectal prolapse is shown by the significant improvement in internal anal sphincter electromyographic frequency and mean resting pressure after successful continence-correcting surgery [7,9,12,20]. It has also been suggested that the external sphincter component plays an important role in incontinence [7,9,12,20,22,29].…”
Section: Continencementioning
confidence: 98%
See 1 more Smart Citation
“…The fact that the internal sphincter plays an important role in continence in rectal prolapse is shown by the significant improvement in internal anal sphincter electromyographic frequency and mean resting pressure after successful continence-correcting surgery [7,9,12,20]. It has also been suggested that the external sphincter component plays an important role in incontinence [7,9,12,20,22,29].…”
Section: Continencementioning
confidence: 98%
“…It has also been suggested that the external sphincter component plays an important role in incontinence [7,9,12,20,22,29]. Duthie and Bartolo [6] suggested that the repair of rectal prolapse improves the anorectal sensation and therefore continence.…”
Section: Continencementioning
confidence: 99%
“…However, up to 40% of patients with an ileoanal pouch experience periodic, often nocturnal fecal incontinence, possibly related to uncoordinated pouch contractions (48). Similarly, rectal prolapse may be associated with fecal incontinence in up to 88% of cases (49)(50)(51). This is most likely due to prolonged inhibition of anal tone from intussusception of the rectum into the upper anal canal.…”
Section: Pathogenic Mechanisms and Etiologymentioning
confidence: 99%
“…As couldb ee xpected, anal incontinence strongly improved (table 4) by removal of the prolapse �hich eliminates dilatation of the anal sphincter muscles. Recoveryo ft he internal anal sphincter as evaluated by electromyogram and anal manometry,h as been demonstrated after rectopexyfor rectal prolapse (18,19). Anal incontinence still continued to improve from first to second evaluation.…”
Section: Discussio�mentioning
confidence: 99%